The word ‘patent’ and its historical use in Polish - Klimek-Grądzka, Jolanta (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The article shows constitutive features of the structural pattern of the lexeme ‘patent’, understood as ‘statutes, legislative acts’ as used in the 18th and the 19th-century Polish. The following nominalizing/verbalizing features are defined as canonical for this structural pattern: 1) sender, 2) recipient, 3) justification for a legal act, 4) content of the regulation, 5) methods of making the law public, 6) spatio-temporal location, 7) locum sigillum and the sender’s signature. Among the secondary features, one can find the following: 1) meta-legal comments, 2) waivers, 3) recitals, 4) law legitimation, 5) indicating the vacatio legis period.